2015
DOI: 10.1007/s13187-015-0884-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Support on Health-Related Quality of Life of Patients with Metastatic Prostate Cancer

Abstract: Patients with metastatic prostate cancer (PC) live longer than patients with metastatic tumours of other sites. Consequently, their social network can influence their quality of life (QoL) during a remarkable life span. The aim of this article is to present the findings of a systematic review of the studies that focused on social network supporting the quality of life of these patients. A systematic review for studies meeting specific criteria was undertaken on three databases. Some level of unmet psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 64 publications
3
19
1
Order By: Relevance
“…These results are consistent with extensive literature on social relationships and health (Berkman & Glass, 2000;Umberson, Crosnoe, & Reczek, 2010), particularly that socially isolated individuals have worse health than those with more social integration and support. For prostate cancer specifically, others have found that lower social support is associated with higher risk of mortality (Jan et al, 2016) and worse QOL (Colloca & Colloca, 2016). The current findings regarding the relatively high prevalence of support received from chosen family and friends versus biologic family is consistent with other work on support and caregiving for gender and sexual minorities (Gabrielson, Holston, & Dyck, 2014), including lesbians with cancer and older adults who identify as a sexual minority.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with extensive literature on social relationships and health (Berkman & Glass, 2000;Umberson, Crosnoe, & Reczek, 2010), particularly that socially isolated individuals have worse health than those with more social integration and support. For prostate cancer specifically, others have found that lower social support is associated with higher risk of mortality (Jan et al, 2016) and worse QOL (Colloca & Colloca, 2016). The current findings regarding the relatively high prevalence of support received from chosen family and friends versus biologic family is consistent with other work on support and caregiving for gender and sexual minorities (Gabrielson, Holston, & Dyck, 2014), including lesbians with cancer and older adults who identify as a sexual minority.…”
Section: Discussionsupporting
confidence: 82%
“…Social support has been widely researched for its implications on increasing quality of life, revealing a correlation between strong social support and improved physical and emotional functioning for cancer survivors (Eton et al, 2001; Kunkel et al, 2000; Campbell et al, 2004; DiIorio et al, 2011; Zhou et al, 2010; Colloca & Colloca, 2015). All of the participants mentioned some form of social support involvement during their cancer survivorship journey, primarily through either unstructured systems, which included romantic partners (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…less anxiety, less depressive symptoms, and a buffer against stress), improved physical functioning (e.g. better symptom control and less pain), decreased mortality, and improved quality of life (Eton et al, 2001; Kunkel et al, 2000; Campbell et al, 2004; Zhou et al, 2010; Colloca & Colloca, 2015; Lafaye et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support can buffer the negative impact of life events on health and positively influence psychosocial adjustment and self-management of chronic illness [35]. A large amount of studies found associations between social support and clinical and self-management/self-care behaviors [36], health-related quality of life [37,38], and patient adherence to treatment [39]. Patient's network for social support includes family and friends, social environment, and all health providers [40].…”
Section: Patient Resourcesmentioning
confidence: 99%